Driving Skills of Individuals With and Without Developmental Coordination Disorder (DCD/Dyspraxia) - Gentle, Judith; Brady, Daniel; Woodger, Nigel; Croston, Sophie; Leonard, Hayley C. (Frontiers in Human Neuroscience, 2021)
Learning to drive is a significant event for the transition to adulthood and delay or avoidance may have social, practical and psychological implications. For those with Developmental Coordination Disorder (DCD/Dyspraxia), driving presents a considerable challenge and the literature shows that there are differences in driving ability between individuals with and without DCD. The aim of the current research is to further our understanding of the mechanisms underlying the driving experiences of individuals with DCD. Nineteen participants with DCD (10 drivers, 9 non-drivers) and 36 controls (17 drivers, 19 non-drivers) aged 18-57 years took part in this study. Participants completed standardised tests, questionnaires and a driving simulation task designed to measure speed, road positioning and rate of change of steering in three experiments with increasing perceptual complexity. Results indicate that behaviours for all participants changed as the perceptual demands of the task increased. However, drivers with DCD were more affected than all other groups, driving more slowly, using more steering adjustments and driving further to the right. These findings illustrate how the impact of both internal and external constraints negatively affect the success of the driving task for individuals with DCD compared to their TD peers.